Kazan Philistines of the First Half of the XIX Century: Children and Childhood in Everyday Life - Victorovna Bessonova, Tatyana; Aleksandrovna Nikolaeva, Valentina (International Journal of Criminology and Sociology, 2022)
The article considers one of the issues of the history of everyday life and family history related to the study of childhood as a stage of life. The study is focused on the philistinism of the city of Kazan in the first half of the XIX century, being the most numerous layer of citizens. The analysis of archival documents allowed us studying such aspects of the daily history of philistinism as the age limits of childhood, attitudes toward children in philistine families, mass behavior and individual decisions, as well as the emotional side of relations between adults and children. The study of the issue allowed us coming to the conclusion that the social status of children, their attitude to childhood and children among the Kazan philistinism largely retain the features inherent in a traditional pre-industrial society. In everyday practices, childhood was not yet perceived as a separately recognized and designated life stage, which was reflected in the philistine’s value system. Philistines often got rid of illegitimate children in many ways, sought to include the child early in the solution of issues of maintaining themselves and the family, as well as removed them from the family by giving them for apprenticeship or working with strangers. However, the predominance of a rational attitude towards childhood did not exclude a positive emotional color in relation to children